Edukasi Bahaya Minuman Manis Kemasan terhadap Kerusakan Ginjal pada Siswa Sekolah Dasar - Kiki Rawitri; Sri Wahyuni; Syilvi Rinda Sari; Ferina Septiani Damanik; Cut Intan Annisa Puteri; Ziza Putri Aisyia Fauzi; Lilik Septiana; Hindri Syahputri (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
Consumption of sugar-sweetened packaged beverages among elementary school children continues to increase and may contribute to various health problems, including kidney damage. Limited knowledge regarding the health risks of sugary beverages is one of the factors contributing to high consumption among children. This community service program aimed to improve students’ knowledge about the dangers of packaged sugary drinks on kidney health through health education activities conducted at SD Ar-Ridha, Biru-Biru District, Deli Serdang Regency. The activity was carried out on November 23, 2024, involving 30 elementary school students. The methods used included interactive lectures, discussions, question-and-answer sessions, and evaluation through pre-test and post-test questionnaires. Educational materials covered types of sugary packaged beverages, added sugar content, kidney function, the effects of excessive sugar intake, and kidney disease prevention efforts. The results demonstrated an increase in participants’ knowledge levels after the educational intervention. The percentage of students categorized as having good knowledge increased from 20.0% during the pre-test to 80.0% during the post-test, while the poor knowledge category decreased from 46.7% to 3.3%. These findings indicate that interactive health education methods are effective in improving students’ understanding of the importance of limiting sugary packaged beverage consumption to maintain kidney health from an early age.